The Analysis of Figure of Speech in Emily Dickinsonâ€™s â€œSuccess Is Counted Sweetestâ€ â€œI Had No Time To Hateâ€, and â€œHave You Got A Brook In Your Little Heartâ€ - Octavia Kurniawati; Masulah - (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2016)
The analysis provides the study about figure of speech, possible meaning and the total meaning in three poemâ€™s of Emily Dickinson â€œsuccess is counted sweetestâ€, â€œ I had no time to hateâ€, Have you got a Brook in your little heartâ€, This study tries to analyze figure of speech, possible meaning and the total meaning in statement of the problem. This analysis aims to analyze the types of figure of speech and possible meaning and to tell the total meaning of the Emily Dickinson poemâ€™s. This analysis explains the design of qualitative method because it is related to the object of research. Qualitative description defines as research designed to produce a low inference description of a phenomenon that draws from discourse. The result of the research of the first poem â€œsuccess is counted sweetestâ€ figure of speech are Metaphor, Hyperbole, symbol, the second â€œ I had no time to hateâ€ , the figure of speech is personification, Symbol. The last poem â€œHave you got a Brook in your little heartâ€ figure of speech is personification, allegory.